KAJIAN NILAI-NILAI PENDIDIKAN AGAMA HINDU DALAM PERTUNJUKAN WAYANG SAPUH LEGER DI SMK NEGERI 3 SUKAWATI - I Gusti Agung Surya Wikrama; Ni Putu Winanti; Ni Made Suyeni (PT. Hasba Edukasi Mandiri, 2026)
The Sapuh leger Puppet Show is one of Bali's cultural heritage which is full of Hindu religious education values, especially those contained in the Murwakala story. This performance not only functions as entertainment, but also as a medium for spiritual, ethical and cultural education for the younger generation. This research is motivated by the importance of efforts to instill an understanding of religious and cultural values in students, especially students majoring in puppetry at SMK Negeri 3 Sukawati. The aim of this research is to determine the form of the Sapuh leger Wayang performance, the educational values contained in the Sapuh leger Wayang performance, and the impact of the Sapuh leger Wayang performance on the younger generation, especially pupils and students at SMK Negeri 3 Sukawati. This research is qualitative research carried out at SMK Negeri 3 Sukawati. The research uses value theory and Structural Functionalism theory. Research data was obtained through observation, interviews and documentation. The results of the research show that the Sapuh leger Wayang performance at SMK Negeri 3 Sukawati is a type of wayang peteng and is held on Tumpek wayang Day. This performance contains Hindu religious education values in the form of tattwa, ethics and ceremonies. Apart from that, Wayang Sapuh leger has a positive impact on students, such as forming good attitudes and behavior, increasing spiritual and social values, preserving local culture, and developing students' talents and creativity.